2018
DOI: 10.18203/2349-2902.isj20180816
|View full text |Cite
|
Sign up to set email alerts
|

New technique for laparoscopic partial splenectomy to decrease blood loss

Abstract: INTRODUCTIONLaparoscopic splenectomy was first performed in 1992 and has since gained popularity, particularly for hematological disorders of the spleen in adult and pediatric patients. Laparoscopic splenectomy is feasible, effective, and safe with low morbidity rates and has rapidly become the surgical approach of choice for patients that require elective splenectomy in the treatment of hematologic disorders. 2,3 That is primarily because patients undergoing laparoscopic splenectomy have less postoperative pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Several studies have reported similar findings. 13,15,17,21 In the current study, the mean hospital stay was 1.2 days. The was no case of postoperative vomiting despite the fact that no preoperative or postoperative anti-emetics.…”
Section: Discussionmentioning
confidence: 53%
“…Several studies have reported similar findings. 13,15,17,21 In the current study, the mean hospital stay was 1.2 days. The was no case of postoperative vomiting despite the fact that no preoperative or postoperative anti-emetics.…”
Section: Discussionmentioning
confidence: 53%